PENERAPAN TEORI PEMBELAJARAN BEHAVIORIS DALAM MENGATASI MASALAH PENDIDIKAN DI INDONESIA - Restia Salviah; M Mamduh Winangun (JURNAL ILMIAH NUSANTARA, 2026)
Education in Indonesia continues to grapple with persistent challenges, including low student learning discipline manifested in frequent tardiness, unfinished assignments, and classroom disruptions and an overreliance on rote memorization methods that prioritize superficial recall over meaningful comprehension and skill development. This library-based research, drawing on an extensive review of national and international journals alongside key texts on educational psychology, examines behaviorist learning theory as a viable strategy to address these issues by fostering structured habits and positive behavioral patterns. Rooted in principles such as stimulus-response association pioneered by Pavlov and refined through Skinner’s operant conditioning, which argues that learning occurs through observable responses shaped by reinforcement—positive (praise, tokens, or privileges for timely task completion) gradually instilling discipline, or negative (removing distractions upon compliance) curbing avoidance behaviors—this approach proves highly relevant in diverse Indonesian school settings where external motivators often outperform intrinsic motivation amid resource constraints. The findings reveal that targeted applications—such as reward schedules within daily routines or immediate feedback loops during lessons—significantly improve student compliance and shift away from rote-heavy practices toward habitual engagement. However, to avoid overemphasizing mechanical repetition at the expense of cognitive processing or emotional growth, educators should adapt behaviorist techniques by layering them with cognitive elements like reflective prompts or affective components such as peer recognition, ensuring a holistic approach that sustains long-term learning outcomes in Indonesian classrooms.